Economics and Finance Readings Selected Papers from Asia-Pacific Conference on Economics & Finance, 2019 - Lau, Evan; Simonetti, Biagio; Trinugroho, Irwan; Tan, Lee Ming (Springer Nature Singapore : Imprint: Springer, 2020)
XII, 124 p. 23 illus.